Transforming Student Character through Christian Religious Education Based on Differentiated Learning - A, Doni; Bilo, Dyulius Thomas (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
The purpose of this study is to answer the issue of character crisis faced by today's students, by explaining the definition of character education and Christian Religious Education, Transformation of character education in Christian Religious Education, the urgency of differentiated learning studies on character education in Christian Religious Education, and the impact of student character transformation through Christian Religious Education based on differentiated learning. For this reason, the method used is qualitative with literature study techniques to analyze relevant literature related to character education and differentiated learning. The findings of this article show that differentiated learning studies can develop students' understanding of Christian values, strengthen spiritual self-awareness, and encourage active involvement in spiritual and social activities. The conclusion of this research makes a significant contribution to Christian Religious Education teachers as educators and students as learners, both theoretically and practically in the field of Christian Religious Education and daily life. In terms of theory, this research enriches the study of the integration of character education in Christian Religious Education with a differentiated learning approach.